Incidence of injuries among professional football players in Spain during three consecutive seasons: A longitudinal, retrospective study - Torrontegui-Duarte, M.; Gijon-Nogueron, G.; Perez-Frias, J. C.; Morales-Asencio, J. M.; Luque-Suarez, A. (Physical Therapy in Sport, 2020)
The aim of the study was to determine risk factors that maybe be associated with a higher incidence of injuries in elite football players in the Spanish league during a three-year follow-up. Injury was defined as a musculoskeletal complaint (pain and/or discomfort) reported by players to the medical staff and receiving medical attention. Design: A longitudinal retrospective study. Setting: and participants: Seventy-one players from Malaga Football Club, who were in the first squad team for three consecutive seasons. Main outcome measures: Incidence, location, severity of injuries were reported according to the Injury Consensus Group for football injuries. Results: Three hundred and fifty six injuries were found, with the highest proportion (44%) being located in the thigh. We found 6.9 (SD 5.87) injuries per 1000 h of match time and 0.23 (SD 0.22) per 1000 h of training. Forwards presented the highest rates in both incidence and severity of injury. Exposure to training was inversely related to the total number of injuries, which means that the greater the exposure to training the lesser the number of injuries. Conclusions: This information can assist clinicians in the identification of risk factors and, thus, the elaboration of prevention programmes that reduce football injuries.